Penentuan Suhu dan Waktu Optimum Metanolisis Minyak Curah dengan Katalisator NaOH - Meilana Dharma Putra (INFO-TEKNIK, 2007)
Crude oil derivate called diesel oil that included as unrenewable fuel mostly is used in industrial and transportation fields. Nowadays, the diesel oil’s demand is increasing. Therefore, alternative sources from renewable raw material such as bio oil for substituting diesel oil from crude oil are very urgent. From this research, we got optimum temperature and optimum time for production bio diesel from crude oil.This research was conducted by react metanolat solution with bio oil in stirred-vessel at atmospheric pressure and certain temperature until required time. The research shows that optimum condition for production bio diesel from crude oil at temperature 40oC and reaction time 80 minutes, with stirrer-velocity 350 rpm and catalyst concentration 1% oil-mass. For this condition, the conversion that we got is 64, 67 %.